Gojek: The New Face of Transportation in the Digital Age - Fathiyah Jamil; Muhtar Muhtar; Suherianto Suherianto (Palakka : Media and Islamic Communication, 2020)
The digital age was born as a result of the development of information and communication technology. The sophistication of digital media provides space for the birth and development of a startup business and it is considered has provided many benefits and conveniences for the community, including in the field of transportation. Gojek is an online transportation business platform that can be well received by the community because it can provide solutions to transportation problems, especially for urban communities. Innovations that combine communication and information technology affect and change people's lifestyles and even shift the existence of online transportation because it is considered more practical. The success of Gojek at the same time proof that now the community is ready to switch into a new lifestyle, an all-digital lifestyle.Keywords: Technology, innovation, Gojek, lifestyle